Fuzzy-Based Efficient Wireless Charging System with Solar PV Interface for Sustainable Transportation - Mr. N Subramanyam; Mr. P R Rajeev; Mr. M Seenivasan; Mr. Pandiyan V (Utilitas Mathematica, 2024)
With the growing demand for sustainable transportation, the integration of renewable energy sources into wireless charging systems has gained significant attention. This paper presents the design and implementation of a fuzzy logic-based efficient wireless charging system with a solar photovoltaic (PV) interface, aimed at enhancing the reliability and sustainability of electric vehicle (EV) charging. The proposed system employs a fuzzy compensation scheme to optimize power transfer efficiency by dynamically adjusting charging parameters based on real-time variations in load and environmental conditions. The solar PV interface ensures a renewable energy supply, reducing dependency on the conventional grid and lowering carbon emissions. The wireless power transfer (WPT) system utilizes resonant inductive coupling to achieve high efficiency while mitigating misalignment issues. The paper proposes the utilization of FLC compensated constant current (CC) and constant voltage (CV) system for PV-integrated static WPT systems. Simulation results validate the effectiveness of the proposed approach, demonstrating improved power transfer efficiency, stability, and adaptability under varying operational conditions.